2020
DOI: 10.1177/0165025420912012
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in associations between early adversity, child temperament, and behavior problems

Abstract: Early adversity is associated with both internalizing and externalizing problems among children, and effects of adversity on dimensions of child temperament may underlie these links. However, very little is known about the role of child sex in these processes. The current study examined whether there are indirect effects of early adversity on behavior problems through dimensions of child temperament and whether these indirect effects vary across child sex. Participants in this multimethod (parent-report survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Additionally, we found, also in accordance with other research ( Ready et al, 2005 ; Else-Quest et al, 2006 ; Cameron Ponitz et al, 2008 ; Else-Quest, 2012 ; Coe et al, 2020 ), differences in relation to the gender of parents and specific temperamental characteristics of girls and boys.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, we found, also in accordance with other research ( Ready et al, 2005 ; Else-Quest et al, 2006 ; Cameron Ponitz et al, 2008 ; Else-Quest, 2012 ; Coe et al, 2020 ), differences in relation to the gender of parents and specific temperamental characteristics of girls and boys.…”
Section: Discussionsupporting
confidence: 93%
“…These nonsignificant mean differences might indicate the cultural differences in the development and acceptance of various character traits of temperament as shown in earlier findings. 6,10 Various differences between US and Pakistani children have been reported. 15 Pakistani children prefer extroverted, practical, and organized styles as compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, behavioural problems were more prevalent in boys than in girls in this study, and behavioural problems were associated with depression. Research has indicated that early adversity influences children's behavioural problems via their temperament, particularly in boys, and children who suffer from early life adversity are at a greater risk for a variety of psychological and emotional disorders 45 …”
Section: Discussionmentioning
confidence: 99%